2021
DOI: 10.1007/s00382-021-06066-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of regional and seasonal variations in Congo Basin precipitation

Abstract: The processes that determine the seasonality of precipitation in the Congo Basin are examined using the atmospheric column moisture budget. Studying the fundamental determinants of Congo Basin precipitation seasonality supports process-based studies of variations on all time scales, including those associated with greenhouse gas-induced global warming. Precipitation distributions produced by the ERA5 reanalysis provide sufficient accuracy for this analysis, which requires a consistent dataset to relate the atm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…The correspondence between E estimates from catchment‐balance, reanalyzes and CMIP6 models shown in Figure 3e suggests that the simulated seasonal cycle in Congo E is relatively robust. E, which might be expected to positively correlate with ρ , broadly follows the same seasonal cycle as precipitation in the Congo (Figure S4b in Supporting Information S1 ), providing essential atmospheric moisture without being the primary driver of precipitation seasonality (Cook & Vizy, 2021 ). An imbalance in E between the two rainfall peaks has been linked to a difference in solar radiation (Burnett et al., 2020 ; Crowhurst et al., 2021 ; Crowhurst et al., 2020 ).…”
Section: Resultsmentioning
confidence: 89%
“…The correspondence between E estimates from catchment‐balance, reanalyzes and CMIP6 models shown in Figure 3e suggests that the simulated seasonal cycle in Congo E is relatively robust. E, which might be expected to positively correlate with ρ , broadly follows the same seasonal cycle as precipitation in the Congo (Figure S4b in Supporting Information S1 ), providing essential atmospheric moisture without being the primary driver of precipitation seasonality (Cook & Vizy, 2021 ). An imbalance in E between the two rainfall peaks has been linked to a difference in solar radiation (Burnett et al., 2020 ; Crowhurst et al., 2021 ; Crowhurst et al., 2020 ).…”
Section: Resultsmentioning
confidence: 89%
“…Notably, the highest rainfall values occur in November, which differs from the pattern observed in the northern part, where they peak in October. Simultaneously, when examining the seasonality of precipitation across the range of 5 S to 5 N (Figure 1c), there is an apparent, though erroneous (Cook & Vizy, 2021), suggestion of a bimodal distribution. A spatial analysis (Figure 2) reveals maximum rainfall in both the eastern and western regions of the Congo Basin during MAM and SON, with ERA5 reanalysis values (Figure 2a,b) showing a slight increase compared to CHIRPS (Figure 2c,d).…”
Section: Assessment Of Era5 Rainfallmentioning
confidence: 99%
“…This comparison focuses on the primary rainy seasons of March-April-May (MAM) and September-October-November (SON). The decision to divide the Congo Basin into various latitudinal levels is informed by prior research (Cook & Vizy, 2021), which demonstrated that this region does not exhibit a clear bimodal rainfall distribution. Specifically, in the Northern Hemisphere latitudinal band of 0 -5 N (Figure 1a), two distinct rainfall maxima are observed in April and October.…”
Section: Assessment Of Era5 Rainfallmentioning
confidence: 99%
“…Finally, we calculate the moisture convergence term (-𝑞 × 𝛻. 𝑉) and moisture transport vectors (𝑞𝑉) at four pressure levels to represent near surface, lower-troposphere, mid-troposphere, and upper troposphere, respectively: 925 hPa, 850 hPa, 700 hPa, and 650 hPa, similar to that in Cook and Vizy (2022) and Nicholson (2022). This is because moisture transport varies substantially between near surface atmosphere, lower troposphere, and middle troposphere, including its source regions.…”
Section: Thermodynamic and Dynamic Equationsmentioning
confidence: 99%
“…Previous studies point to atmospheric hydrodynamics as key controlling factors in determining seasonal rainfall (e.g., Cook and Vizy, 2022). Low-level divergence within the equatorial region during the rainy seasons shows that the Intertropical Convergence Zone does not play a strong role in determining the seasonal migration of rainfall (Nicholson, 2018, Yang et al, 2015.…”
Section: Introductionmentioning
confidence: 99%